PESTICIDES BIOACCUMULATION AND THEIR SOIL POLLUTANT EFFECT - Othman, B. A.; Kakey, E. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to investigate pesticides bioaccumulation and their soil pollutant effect. The experiment was included sixteen active greenhouses in Erbil plane, and conducted during September 2017 and March 2018. The present study revealed that the pesticides residue of pyridabine, thiamethoxam, abamectin and spirodiclofen were detected in greenhouse soil samples. The values of soil heavy metals contaminations factor (CF) revealed, that the studied greenhouse soil samples were ranged from low to very high contamination, while for pesticides were ranged from non to high contaminated. Soil pollution load index results supported that, the greenhouse soil was contaminated especially by Cr, Ni and Co. Pollution load index (PLI) was ranged from 7.751 to 0.303; supporting that the soils were contaminated in most sites. It could be concluded that, significant need for the development of pollution prevention and scientific strategies to reduce heavy metal pollution and pesticide accumulation residuals within greenhouses in Erbil plane.